2020
DOI: 10.1063/5.0008060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polarization characteristics in metal/ferroelectric/semiconductor capacitors and ferroelectric field-effect transistors

Abstract: In this study, we propose a measurement technique for evaluating ferroelectric polarization characteristics in ferroelectric field-effect transistors (FeFETs). Different from standard metal/ferroelectric/metal capacitors, the depletion and inversion phenomena in semiconductor substrates have to be carefully taken into account when evaluating the ferroelectric properties using fast voltage sweep as input. The non-equilibrium deep depletion is found to be the limiting factor for the accurate evaluation of ferroe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 39 publications
2
25
1
Order By: Relevance
“…Numerous studies conducted in several research groups in the last decade have demonstrated that fluorite‐structure ferroelectrics can be deposited using various deposition techniques such as ALD, sputtering, pulsed laser deposition (PLD), chemical vapor deposition (CVD), and chemical solution deposition (CSD). [ 1–19,22–54 ] Among these techniques, ALD was the most intensively studied deposition technique because it can form very thin conformal and uniform ferroelectric films based on a self‐limiting mechanism by chemical reactions between metal precursors, oxygen source, and the previously deposited film (or substrate). In this regard, the only controllable parameters during the ALD process are types of metal precursor/oxygen sources, [ 27–29 ] pulse/purge time, [ 30,31 ] and deposition temperature.…”
Section: Deposition Methods For Low‐thermal‐budget Ferroelectric Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies conducted in several research groups in the last decade have demonstrated that fluorite‐structure ferroelectrics can be deposited using various deposition techniques such as ALD, sputtering, pulsed laser deposition (PLD), chemical vapor deposition (CVD), and chemical solution deposition (CSD). [ 1–19,22–54 ] Among these techniques, ALD was the most intensively studied deposition technique because it can form very thin conformal and uniform ferroelectric films based on a self‐limiting mechanism by chemical reactions between metal precursors, oxygen source, and the previously deposited film (or substrate). In this regard, the only controllable parameters during the ALD process are types of metal precursor/oxygen sources, [ 27–29 ] pulse/purge time, [ 30,31 ] and deposition temperature.…”
Section: Deposition Methods For Low‐thermal‐budget Ferroelectric Filmsmentioning
confidence: 99%
“…Depending on the type of material, the formation of the ferroelectric phase during the annealing process (or partially during the ALD process) can be enhanced by controlling the applied stress due to the difference in the thermal expansion coefficient or increasing the concentration of oxygen vacancies at the interface by the oxygenscavenging effect. [2,4,5,[47][48][49][50][51][52] In this regard, the influence of various bottom electrodes on ferroelectric properties has been extensively studied based on the metal-ferroelectric-metal (MFM) structure. [47][48][49][50][51] According to the experimental results reported in the past decade, the use of TiN bottom electrodes could be a useful strategy to improve the ferroelectric properties of Hf 1-x B x O 2 films.…”
Section: Substrate Materials For Low-thermal-budget Ferroelectric Fil...mentioning
confidence: 99%
See 1 more Smart Citation
“…To prove the ferroelectric behavior of the 5-nm-thick ferroelectric layer, grazing incident X-ray diffraction (GIXRD) (PANalytical, Malvern, United Kingdom) and positiveup-negative-down (PUND) measurement were performed. Figure 4a presents the GIXRD analysis of the 5-nm-thick HZO film annealed at 500 • C for 30 s. The GIXRD pattern of ALD HZO showed strong peaks at approximately 30 • and 35 • that corresponded to the ferroelectric orthorhombic phase with space group Pbc2 1 [20]. Figure 4b presents the polarizationvoltage (P-V) curve measured by the PUND method for the metal/ferroelectric/insulator/ semiconductor (MFIS) capacitor with 5 nm HZO after RTA at 500 • C for 30 s, which was the same condition as used for the fabricated devices.…”
Section: Resultsmentioning
confidence: 99%
“…In FeCAPs, P-V loops are mostly derived indirectly through monitoring of the current through the stack when applying triangular-shaped voltage inputs. Conversely, in FeFETs characterization of the P-V loop differs from that of MFM stacks (even for the same ferroelectric material and thickness) because of incomplete charge screening and influence of underlying and capping layers on the FE-HfO2 [164]. In fact, relatively low doping of the semiconductor body in FeFETs can cause the deep-depletion effect, that impedes the formation of the inversion layer required to screen the polarization charge and thus to correctly characterize the P-V loop [164].…”
Section: A P-v Loop Measurementsmentioning
confidence: 99%